Language across disciplinary boundaries - Mantero, Miguel; Miller, Paul Chamness; Watzke, John L. (Readings in language studies, 2021)
The International Society for Language Studies (ISLS) inaugurates its first volume in the series Readings in Language Studies with Language Across Disciplinary Boundaries, a text that represents international perspectives on language and identity, critical pedagogy, language and power, perspectives on second language acquisition and teacher education. Founded in 2002, ISLS is a world-wide organization of volunteers, scholars and practitioners committed to critical, interdisciplinary, and emergent approaches to language studies.